Sociologie et sciences de l’environnement : à la recherche de prises communes autour de tensions épistémiques irréductibles. Entretien avec Francis Chateauraynaud - Anthony Pecqueux; Perrine Poupin; Francis Chateauraynaud (Tracés, 2022)
This interview with Francis Chateauraynaud takes as its starting point his extraordinary ability to move between disciplines, identify areas of epistemic tension, and make links between rationales of reasoning and proof. This interview is, therefore, less concerned with tracing a career chronologically than with presenting possible, and very practical common measures, particularly opening up spaces for discussion: long-term seminars, critical discussions, and also relevant comments in publications. It outlines an interdisciplinarity based on pragmata: actions, things, practices - not slogans. It is not about sticking to “principles” or following what is really happening in theory; it only involves giving precedence to a principle of access and description, through experience.